Exploring the Underlying Factors Influencing Help-Seeking Avoidance Among University Students - Novak, Mateja; Kovács, Eszter (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to explore the underlying psychological, cultural, institutional, and cognitive factors that contribute to help-seeking avoidance among university students.Methods and Materials: Using a qualitative phenomenological design, semi-structured interviews were conducted with 29 university students from various institutions across Hungary. Participants were recruited through purposive sampling, and interviews continued until theoretical saturation was achieved. The interviews focused on students’ personal experiences and perceptions regarding barriers to academic or psychological help-seeking. Data were transcribed verbatim and analyzed using thematic analysis supported by NVivo software. Codes and themes were inductively derived through a six-phase process involving open coding, theme development, and analytic memoing to ensure trustworthiness and rigor.Findings: Four major themes emerged: (1) Perceived Social and Cultural Barriers, including stigma, family norms, and peer group expectations; (2) Emotional and Psychological Factors, such as fear of vulnerability, self-stigma, emotional suppression, and trust deficits; (3) Institutional and Structural Constraints, including limited access, confidentiality concerns, and inadequate outreach; and (4) Personal Beliefs and Cognitive Barriers, such as belief in self-reliance, minimization of distress, and skepticism about help effectiveness. Participants consistently described a complex interplay of internalized attitudes, environmental cues, and cultural narratives that reinforced avoidance behaviors. Several students cited prior negative experiences and mistrust in university services as key deterrents.Conclusion: To address these issues effectively, universities must implement culturally sensitive, accessible, and stigma-reducing mental health strategies that reshape peer norms and institutional practices.